Experimental Validation of Vehicle Dynamic Characteristics of a Virtual Heavy Vehicle Model / I. Nurzaki ...[et al.] - Nurzaki, I.; Abdullah, A. Saifizul; Ramli, R. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The experimental approach is usually used as a way to test, modify or optimize vehicle sub-system characteristics. This approach is a time-consuming process, costly and with various limitations. To avoid that, a simulation approach is used. However, to rely on the software, the simulation model has to be validated with the actual vehicle before it can be used for further virtual complex testing. In this paper, a validation of dynamic characteristics for full virtual heavy vehicle model with experimental results of an actual heavy vehicle is performed. The virtual heavy vehicle model was developed based on ISUZU FSR two-axle Single Unit Truck (SUT) using a multi-body dynamic software. The development process of the model can be divided into three parts; which are, the development of virtual heavy vehicle model, road design configuration, and driver and maneuvering setup. All data information to develop and simulate the virtual heavy vehicle model is taken from the actual experimental setup. The heavy vehicle will maneuver with a maximum velocity of 40 km/h on four (4) selected test field locations located at Lingkungan Budi route, Universiti of Malaya, Malaysia. The vehicle dynamic behaviors such as lateral acceleration and vehicle speed were observed during simulation and compared with the experimental data for the verification process. It is concluded that the trends between simulation and the experimental result were found to be almost similar with an acceptable level of percentage error.